El secreto de un estadounidense en la tierra de los incas: caracterización de la praxis cultural de Albert A. Giesecke en el Perú a partir del filme El secreto de los incas (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
Albert A. Giesecke (USA, 1883-Peru, 1968) arrived in Peru in 1909 as a member of the team in charge of educational reform during the first government of Augusto B. Leguía. After working in various educational institutions, he was appointed rector of the University of Cuzco (1910-1923) and later elected mayor of the city (1920-1923). Based on the analysis of the representation of American subjects in the film Secret of the Incas (1954), this essay seeks to characterize the Gieseckian style of cultural policies. In the first part, his arrival in Perú is contextualized in order to understand the complex political situation that the young American encountered. In the second part, the analysis of the film shows different ways of being an American in Cuzco, challenging the stereotype of the “gold-digger gringo” and offering a profile of an American capable of passionately defending and promoting the culture of his adopted homeland.
Keywords: Cuzco; Secret of the Incas; Albert Giesecke; cultural policies; Pareto